Correction to: Treatment of acute Achilles tendon rupture - a multicentre, non-inferiority analysis - Olof Westin; Tony Sjögren; Simon Svedman; Alexandra Horvath; Eric Hamrin Senorski; Kristian Samuelsson; Paul Ackermann (BMC Musculoskeletal Disorders, 2021)
An amendment to this paper has been published and can be accessed via the original article.